Microwave-assisted extraction of carvone from carum carvi - Borole, O. D.; Shirsath, S. R.; Gaikwad, S. G. (Novel water treatment and separation methods simulation of chemical processes, 2017)
Due to increasing demand for potable and irrigation water, new scientific research is being conducted to deal with wastewater from a variety of sources. Novel Water Treatment and Separation Methods: Simulation of Chemical Processes presents a selection of research related to applications of chemical processes for wastewater treatment, separation techniques, and modeling and simulation of chemical processes. Among the many topics are: degradation of herbicide removal of anionic dye efficient sun-light driven photocatalysis removal of copper and iron using green activated carbon defluoridation of drinking water removal of calcium and magnesium from wastewater using ion exchange resins degradation of vegetable oil refinery wastewater novel separation techniques, including microwave-assisted extraction and more The volume presents selected examples in wastewater treatment, highlighting some recent examples of processes such as photocatalytic degradation, emulsion liquid membrane, novel photocatalyst for degradation of various pollutants, and adsorption of heavy metals. The book goes on to explore some novel separation techniques, such as microwave-assisted extraction, anhydrous ethanol through molecular sieve dehydration, batch extraction from leaves of Syzygium cumini (known as jambul, jambolan, jamblang or jamun), and reactive extraction. These novel separation techniques have proved be advantageous over conventional methods. The volume also looks at modeling and simulation of chemical processes, including chapters on flow characteristics of novel solid-liquid multistage circulating fluidized bed, mathematical modeling and simulation of gasketed plate heat exchangers, optimization of the adsorption capacity of prepared activated carbon, and modeling of ethanol/water separation by pervaporation, along with topics on simulation using CHEMCAD software.